Impact of Colonizer Copepods on Zooplankton Structure and Diversity in Contrasting Estuaries. - Barroeta, Z., F. Villate, I. Uriarte & A. Iriarte (Estuaries And Coasts, 2022)
The impact of the occurrence of the non-indigenous species (NIS) Acartia tonsa, Oithona davisae, and Pseudodiaptomus marinus and of the range-expanding copepods Acartia bifilosa and Calanipeda aquaedulcis on the structure and diversity of zooplankton communities was analyzed using 18 years (1998–2015) time series from the contrasting estuaries of Bilbao and Urdaibai (Basque coast, Bay of Biscay). Changes in the structure of communities were assessed by using multivariate analyses of taxa abundances and changes in diversity by using descriptors of alpha, beta, and gamma diversity. The most evident changes occurred at the upper reaches of the estuary of Bilbao, where an abundant and less diverse brackish community, dominated by the NIS, A. tonsa and O. davisae, succeeded a low abundance and more diverse community of neritic origin. The later establishment of C. aquaedulcis was linked to further changes in the structure of the community and a progressive increase in diversity. The seasonal pattern of diversity at the inner estuary and the beta diversity in the estuary were also significantly affected by the arrival of the NIS and C. aquaedulcis. In contrast, the original low diversity brackish community of the estuary of Urdaibai, clearly dominated by A. bifilosa, was far less affected by the arrival of the same copepod NIS, and A. bifilosa remained as the species best related to the changes in zooplankton structure and diversity in the brackish habitats of the estuary.